Tonic extracellular glutamate and ischaemia: glutamate antiporter system xc− regulates anoxic depolarization in hippocampus. (30th November 2022) - Heit, Bradley S.; Chu, Alex; Sane, Abhay; Featherstone, David E.; Park, Thomas J.; Larson, John
Abstract : Abstract: In stroke, the sudden deprivation of oxygen to neurons triggers a profuse release of glutamate that induces anoxic depolarization (AD) and leads to rapid cell death. Importantly, the latency of the glutamate‐driven AD event largely dictates subsequent tissue damage. Although the contribution of synaptic glutamate during ischaemia is well‐studied, the role of tonic (ambient) glutamate has received far less scrutiny. The majority of tonic, non‐synaptic glutamate in the brain is governed by the cystine/glutamate antiporter, system xc − . Employing hippocampal slice electrophysiology, we showed that transgenic mice lacking a functional system xc − display longer latencies to AD and altered depolarizing waves compared to wild‐type mice after total oxygen deprivation. Experiments which pharmacologically inhibited system xc −, as well as those manipulating tonic glutamate levels and those antagonizing glutamate receptors, revealed that the antiporter's putative effect on ambient glutamate precipitates the ischaemic cascade. As such, the current study yields novel insight into the pathogenesis of acute stroke and may direct future therapeutic interventions. Key points: Ischaemic stroke remains the leading cause of adult disability in the world, but efforts to reduce stroke severity have been plagued by failed translational attempts to mitigate glutamate excitotoxicity. Elucidating the ischaemic cascade, which within minutes leads to irreversible tissue damage induced by anoxic depolarization, must be a principal focus. Data presented here show that tonic, extrasynaptic glutamate supplied by system xc − synergizes with ischaemia‐induced synaptic glutamate release to propagate AD and exacerbate depolarizing waves. Exploiting the role of system xc − and its obligate release of ambient glutamate could, therefore, be a novel therapeutic direction to attenuate the deleterious effects of acute stroke. Abstract : Abstract figure legend Tonic, extrasynaptic glutamate synergizes with synaptically released glutamate to propagate anoxic depolarization (AD). Mice lacking system xc − (xCT −/− ), an astrocytic glutamate antiporter, exhibit 60–80% lower tonic extracellular glutamate concentrations compared to wild‐type controls. Under anoxic challenge, wild‐type mice experience excessive presynaptic (Pre) glutamate release, which synergizes with extrasynaptic glutamate to rapidly flood the extracellular space. This activates postsynaptic (Post) AMPA and NMDA receptors, thus precipitating AD, enhancing depolarizing AD waves and provoking the loss of membrane potentials. Despite a greater abundance of postsynaptic AMPA receptors, these ischaemia‐driven events are significantly mitigated in xCT −/− mice due to the decrement of tonic glutamate. This ultimately reduces the accumulation of extracellular glutamate during anoxia, delays AD and attenuates depolarizing AD waves in xCT −/− mice. Importantly, both genetic deletion and pharmacological inhibition of system xc − produce this ischaemic neuroprotection. Generated using BioRender (www.biorender.com ).